The Influence of Service Quality and Price on Purchasing Decisions at the Azalea Pharmacy, Sukabumi City - Shelma Marina Salsyabila; Rully Moch. Ichsan (Formosa Journal of Social Sciences (FJSS), 2024)
This study took place in Sukabumi City at the Azalea Pharmacy. The study's objective is to find out how customers in Sukabumi City's Azalea Pharmacy feel about the store's pricing and service quality in relation to their final purchase choice. The study methodologies employed included both descriptive and associative analysis. One hundred individuals were selected using a non-probability, purposive selection technique to represent the demographic of customers who frequently purchase goods and services at the Azalea Pharmacy in Sukabumi City. You may put the tool through its paces by doing tests for validity, reliability, and classical assumption. After that, we may go on to multiple linear analysis, partial t-test, simultaneous f-test, study of the coefficient of determination, and effects of multiple correlation. According to the results of the correlation analysis, there is a strong correlation between service quality and purchasing decisions (r=0.723, or 72.3%), which falls within the range of 0.600-0.799. Similarly, there is a strong correlation between price and purchasing decisions (r=0.755, or 75.5%), once again falling within the range of 0.600-0.799. The determination analysis reveals that service quality and price significantly impact purchase decisions (Rsquared = 0.623, or 62.3%). Other variables, not included in this study, account for the remaining 37.7%